Analisis Penjadwalan Proyek Produksi Kubah Masjid di UD. XYZ - Maharani, Sani Zakiyah; Satoto, Handy Febri (Fakultas Teknik UMRI, 2025)
UD XYZ is experiencing delays in the construction of the mosque dome due to increased market demand and design complexity. Previously, the company used the bar chart method, which was less effective in depicting the relationships between activities and identifying the critical path. Therefore, this study proposes an alternative approach using the PERT and CPM methods to improve project scheduling efficiency. The analysis results show that the CPM method successfully identified the critical path in activities A-B-C-D-K-M-N-O-P. Meanwhile, the PERT method estimates the project to be completed in 73 days with a 50% probability, and 74 days with an 80% probability.